2022
DOI: 10.1155/2022/2905663
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on G-Quadruplexes in Human Telomeres and Human Telomerase Reverse Transcriptase (hTERT) Promoter

Abstract: The upregulation telomerase activity is observed in over 85-90% of human cancers and provides an attractive target for cancer therapies. The high guanine content in the telomere DNA sequences and the hTERT promoter can form G-quadruplexes (G4s). Small molecules targeting G4s in telomeres and hTERT promoter could stabilize the G4s and inhibit hTERT expression and telomere extension. Several G4 ligands have shown inhibitory effects in cancer cells and xenograft mouse models, indicating these ligands have a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…For example, TERT promoter methylation is counterintuitively correlated with chromatin accessibility and TERT expression ( Salgado et al, 2020 ; Liu et al, 2023 ). Also, the formation of G-quadruplexes in the G-rich region of the promoter has a major influence on the expression of TERT , and mutations in the G-rich region of the promoter may lead to disruption of their structure which in turn strongly affects transcription factor binding and enhances TERT expression ( Gu et al, 2022 ; Pavlova et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TERT promoter methylation is counterintuitively correlated with chromatin accessibility and TERT expression ( Salgado et al, 2020 ; Liu et al, 2023 ). Also, the formation of G-quadruplexes in the G-rich region of the promoter has a major influence on the expression of TERT , and mutations in the G-rich region of the promoter may lead to disruption of their structure which in turn strongly affects transcription factor binding and enhances TERT expression ( Gu et al, 2022 ; Pavlova et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, TERT can act as a modulator in NF-kB and Wnt/β-catenin signaling pathways ( Li and Tergaonkar, 2014 ). Other non-canonical functions of TERT include regulation of apoptosis, maintenance of the cellular redox homeostasis, cell proliferation, response to DNA damage, and formation of G-quadruplexes in the G-rich area of gene promoters, which can influence transcription by regulating binding of transcription factor proteins ( Fleisig et al, 2016 ; Khattar et al, 2016 ; Yuan et al, 2019 ; Rosen et al, 2020 ; Gu et al, 2022 ; Pavlova et al, 2022 ; Palamarchuk et al, 2023 ). Thus, theoretically TERT promoter mutations may also affect these and probably other processes related to TERT .…”
Section: Introductionmentioning
confidence: 99%
“…It contains two essential subunits: human telomerase reverse transcriptase (hTERT) and the RNA subunit human telomerase RNA (hTERC). Upregulation of telomerase activity is observed in over 85–90% of human cancers; thus, targeting telomerase is an attractive approach [ 94 ].…”
Section: Immunotherapy For T-allmentioning
confidence: 99%
“…The hTERT promoter, which contains many G-tracts on the same DNA strand, exhibits an exceptional potential for G-quadruplex formation [14,15]. The formation of G-quadruplexes in the hTERT promoter has been shown to inhibit hTERT expression, leading to telomere shortening and senescence [16]. Recent studies have also suggested that G-quadruplexes in the hTERT promoter can play a role in hTERT activation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%